2014
DOI: 10.1186/2193-1801-3-42
|View full text |Cite
|
Sign up to set email alerts
|

Rich and purposeful mathematical knowledge of mothers and children in a Torres Strait Islander community

Abstract: This paper focuses on a pilot study that explored the situated mathematical knowledge of mothers and children in one Torres Strait Islander community in Australia. The community encouraged parental involvement in their children’s learning and schooling. The study explored parents’ understandings of mathematics and how their children came to learn about it on the island. A funds of knowledge approach was used in the study. This approach is based on the premise that people are competent and have knowledge that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Six studies identified funds of knowledge of local communities, focusing on STEM ideas and practices related to their cultural practices (Albrecht & Upadhyay, 2018;Alvaré, 2017;Ewing, 2014;Handa & Tippins, 2013;Harper, 2016;Svarovsky et al, 2017). Studies often involved researchers physically entering community spaces, which is crucial to the ethnographic methods used in Moll et al (1992).…”
Section: Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Six studies identified funds of knowledge of local communities, focusing on STEM ideas and practices related to their cultural practices (Albrecht & Upadhyay, 2018;Alvaré, 2017;Ewing, 2014;Handa & Tippins, 2013;Harper, 2016;Svarovsky et al, 2017). Studies often involved researchers physically entering community spaces, which is crucial to the ethnographic methods used in Moll et al (1992).…”
Section: Identificationmentioning
confidence: 99%
“…Somali mothers who participated in the study viewed science as more useful when it connected to their home practices. Two studies identified community funds of knowledge related to village fishing practices (Ewing, 2014;Handa & Tippins, 2013). In Ewing (2014), Torres Strait Islanders shared community practices of dividing fish among family members, which involved the mathematical practices of sorting and partitioning.…”
Section: Identificationmentioning
confidence: 99%
See 1 more Smart Citation